The Manufacture of Xeno- and Feeder-Free Clinical-Grade Human Embryonic Stem Cell Lines: First Step for Cell Therapy - Souralova, Tereza; Rehakova, Daniela; Jeseta, Michal; Tesarova, Lenka; Beranek, Jindrich; Ventruba, Pavel; Hampl, Ales; Koutna, Irena (International journal of molecular sciences, 2022)
Human embryonic stem cells (hESCs) are increasingly used in clinical trials as they can change the outcome of treatment for many human diseases. They are used as a starting material for further differentiation into specific cell types and to achieve the desirable result of the cell therapy; thus, the quality of hESCs has to be taken into account. Therefore, current good manufacturing practice (cGMP) has to be implemented in the transport of embryos, derivation of inner cell mass to xeno-free, feeder-free and defined hESC culture, and cell freezing. The in-depth characterization of hESC lines focused on safety, pluripotency, differentiation potential and genetic background has to complement this process. In this paper, we show the derivation of three clinical-grade hESC lines, MUCG01, MUCG02, and MUCG03, following these criteria. We developed and validated the system for the manufacture of xeno-free and feeder-free clinical-grade hESC lines that present high-quality starting material suitable for cell therapy according to cGMP.
Keywords: Cell Line; clinical grade; lidské embryonální kmenové buňky; buněčná diferenciace; buněčné kultury; hESC; Embryonic Stem Cells; embryonální kmenové buňky; buněčná a tkáňová terapie; clean rooms; lidé; Cell- and Tissue-Based Therapy; pluripotent stem cells; Humans; cell therapy; Cell Culture Techniques; buněčné linie; Human Embryonic Stem Cells; Cell Differentiation